Macrophage Migration Inhibitory Factor (MIF) Is Essential for Type 2 Effector Cell Immunity to an Intestinal Helminth Parasite - Filbey, Kara J.; Varyani, Fumi; Harcus, Yvonne; Hewitson, James P.; Smyth, Danielle J.; McSorley, Henry J.; Ivens, Alasdair; Nylén, Susanne; Rottenberg, Martin; Löser, Stephan; Maizels, Rick M. (Frontiers in Immunology, 2019)
Immunity to intestinal helminths is known to require both innate and adaptive components of the immune system activated along the Type 2 IL-4R/STAT6-dependent pathway. We have found that macrophage migration inhibitory factor (MIF) is essential for the development of effective immunity to the intestinal helminth Heligmosomoides polygyrus, even following vaccination which induces sterile immunity in wild-type mice. A chemical inhibitor of MIF, 4-IPP, was similarly found to compromise anti-parasite immunity. Cellular analyses found that the adaptive arm of the immune response, including IgG1 antibody responses and Th2-derived cytokines, was intact and that Foxp3+ T regulatory cell responses were unaltered in the absence of MIF. However, MIF was found to be an essential cytokine for innate cells, with ablated eosinophilia and ILC2 responses, and delayed recruitment and activation of macrophages to the M2 phenotype (expressing Arginase 1, Chil3, and RELM-α) upon infection of MIF-deficient mice; a macrophage deficit was also seen in wild-type BALB/c mice exposed to 4-IPP. Gene expression analysis of intestinal and lymph node tissues from MIF-deficient and -sufficient infected mice indicated significantly reduced levels of Arl2bp, encoding a factor involved in nuclear localization of STAT3. We further found that STAT3-deficient macrophages expressed less Arginase-1, and that mice lacking STAT3 in the myeloid compartment (LysMCrexSTAT3fl/fl) were unable to reject a secondary infection with H. polygyrus. We thus conclude that in the context of a Type 2 infection, MIF plays a critical role in polarizing macrophages into the protective alternatively-activated phenotype, and that STAT3 signaling may make a previously unrecognized contribution to immunity to helminths.